Fully physical double network gel based on low hydrolysis degree poly(vinyl alcohol) - Ha Ngoc Giang; Thanh Thai Nguyen; Thu Thi Trang Luu; Anh Thi Ngoc Pham; Tuan Nguyen Anh Huynh (eXPRESS Polymer Letters, 2025)
Freeze-thaw (F-T) poly(vinyl alcohol) (PVA) as a soft network and ionic-crosslinked sodium carboxymethyl cellulose (CMC) as a hard network were applied to fabricate a double network (DN) gel using a one-step process. Mechanical properties of the DN gel using a high degree of hydrolysis PVA (PVA-CMC of 60-1) were significantly improved compared to that of a single network gel of PVA. The tensile strength of ~0.55 MPa and elongation at break of 179% could be achieved. The mechanical properties of PVA-poly(acrylic acid) DN gel were lower than that of PVA-CMC samples. Fourier-transformed infrared (FTIR) spectroscopy results showed less compatibility between polyacrylic acid (PAA) and PVA compared to that of CMC. The solution made from the lower hydrolysis degree PVA (PVA1788) could form a strong gel after being treated with NaOH 1 M. The FTIR result showed the disappearance of acetate groups. A large melting peak in differential scanning calorimetry (DSC) results showed high crystallinity of the hydrolyzed-PVA1788. The effect of various multivalent cations on the mechanical properties of PVA1788-CMC DN gel was performed. The properties of the samples followed the order: Fe3+<Co2+<Ni2+<Cu2+<Zn2+<Ca2+~Ba2+<Al3+. The tensile strength of DN gel fabricated using AlCl3 solution could reach 0.87 MPa, and the elongation at break was 330%.